Integrating Artificial Intelligence and Case-Based Learning in Designing Pragmatic Speech Strategy Assessment Instruments - Putri Aulia Nurhuda (Universitas Pakuan, 2025)
This study aims to develop and validate an innovative assessment instrument that integrates artificial intelligence (AI) and case-based learning to measure students’ understanding of pragmatic speech strategies in higher education. The research adopts a research and development (RD) approach based on the 4-D model, focusing on the stages of define, design, and develop. Data were collected through needs analysis questionnaires, expert validation sheets, and documentation involving students and lecturers from the Indonesian Language and Literature Education program. The instrument was designed to incorporate contextual case scenarios supported by AI to enhance analytical and reflective thinking in pragmatic communication. The validation results indicate that the instrument achieved a content validity score of 77.5% (valid), linguistic validity of 84.61% (very valid), and graphical feasibility of 88.46% (very valid), with an overall validity score of 83.52%, categorized as highly valid. These findings demonstrate that the integration of AI and case-based learning provides a contextual, adaptive, and effective evaluation tool for assessing students’ pragmatic competence. The study concludes that AI-assisted assessment instruments can significantly enhance the quality of learning evaluation by promoting higher-order thinking skills and contextual language use, although further empirical testing is recommended to measure their impact on learning outcomes.